PERBANDINGAN PERAMALAN (FORECASTING) MENGGUNAKAN ANALISA TEKNIKAL MOVING AVERAGE DAN FIBONACCI PADA PERGERAKAN TRANSAKSI GOLD (XAU) - Trisilo, Rismanto Gatot; Christanti, Paramitha Lea; Aji, Ambyah Atas (Surakarta Management Journal, 2020)
AbstractThe investment business currently attracts quite a lot of investors who transact on foreign exchange or forex, because it is quite high and fast to get profits, especially on the movement of XAUUSD or gold commodities, high volatility that attracts investors and investment managers to direct it to this commodity.With technical analysis using moving averages and Fibonacci in order to maximize large profits, so that research will compare the two at different time frames, and later investors can use it to become a guide for using these two technical analyzes and the result is that both can maximize profits by using MA rather than Fibonacci, the shortcomings of this study are not using fundamental analysis only with qualitative research methods. Hopefully this can help and future research can be directed to behavior finance.Keyword :Forex, Technical analysis, Gold, Moving Average, Fibonacci